2015
DOI: 10.1097/mot.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of alloimmunity of the intestinal graft

Abstract: Ischemia-reperfusion, surgical injury, and bacterial translocation trigger the innate immune system, starting acute rejection. Interaction between donor and recipient immune cells generate injury and tolerance, which occur mostly in secondary lymphoid organs, lamina propria, and epithelium. Chronic rejection mostly affects the endothelial cells, generating graft dysfunction. DSA increase the risk of graft rejection both acutely and chronically, and the liver protects against their effects. Induction therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…31 Increase in crypt enterocyte apoptosis is 1 characteristic feature of small bowel rejection. [32][33][34] Glucose absorption takes place in villous epithelium, consequently, our observation may indicate that villous enterocytes are also affected by initial rejection events. Lymphocytes suffer from several important metabolic changes upon activation, with an increase in glycolysis being one of the most constant features.…”
Section: Figurementioning
confidence: 89%
“…31 Increase in crypt enterocyte apoptosis is 1 characteristic feature of small bowel rejection. [32][33][34] Glucose absorption takes place in villous epithelium, consequently, our observation may indicate that villous enterocytes are also affected by initial rejection events. Lymphocytes suffer from several important metabolic changes upon activation, with an increase in glycolysis being one of the most constant features.…”
Section: Figurementioning
confidence: 89%
“…To investigate DST mechanisms, secondary skin transplant had often been used because of its relatively simple procedure and because it was easy to observe. 32,33 However, skin is not a vascularized organ, and the mechanisms of DST induction in skin allograft might be different from vascularized organs, 33,34 such as in the heart. In this study, a novel treatment regimen was established, using tacrolimus and rapamycin as a sequential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of chronic rejection resulting from graft tissue injury are multifactorial and both immune- and non-immune-mediated factors can contribute to graft injury. Emerging evidence suggests that immune-mediated injuries to the graft are the fundamental cause of chronic rejection[ 3 , 52 ]. Several studies have identified severe acute rejection, recurrent episodes of rejection, the cumulative burden of acute rejection, and late-onset acute rejection as risk factors for chronic rejection[ 6 , 21 ].…”
Section: Chronic Rejectionmentioning
confidence: 99%
“…The intestine is often deemed one of the most difficult organs to be transplanted because of its unique structure and enhanced immune response[ 1 - 3 ]. Over the past several decades, intestinal transplantation (ITx) has achieved remarkable advancement not only in volume of transplants but also in outcomes, owing to progress in various aspects of organ preservation, surgical technique, immunosuppression, and postoperative management[ 4 - 7 ].…”
Section: Introductionmentioning
confidence: 99%